\[\boxed{\text{650\ (650).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1) - x^{2} - 16x + 36 =\]
\[= - \left( x^{2} + 16x + 64 - 100 \right) =\]
\[= - (x + 8)^{2} + 100\]
\[принимает\ наибольшее\ \]
\[значение\ при\ x = - 8 \Longrightarrow\]
\[\Longrightarrow 0 + 100 = 100\]
\[2)\ 2 - 16x^{2} + 24x =\]
\[= - \left( 16x^{2} - 24x + 9 - 11 \right) =\]
\[= - (4x - 3)^{2} + 11\]
\[принимает\ наибольшее\ \]
\[значение\ при\ 4x - 3 = 0;\ \ \]
\[x = \frac{3}{4} \Longrightarrow 0 + 11 = 11\]
\[\boxed{\text{650.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ x^{6} = \left( x^{3} \right)^{2}\]
\[2)\ y^{4} = \left( y^{2} \right)^{2}\]
\[3)\ 4x^{2} = (2x)^{2}\]
\[4)\ \frac{1}{9}x^{4} = \left( \frac{1}{3}x^{2} \right)^{2}\]
\[5)\ a^{8}b^{10} = \left( a^{4}b^{5} \right)^{2}\]
\[6)\ 0,36x^{2}y^{12} = \left( 0,6xy^{6} \right)^{2}\]
\(7)\ 1,21m^{10}n^{20} = \left( 1,1m^{5}n^{10} \right)^{2}\)
\[8)\ 1\frac{9}{16}a^{14}b^{16} = \frac{25}{16}a^{14}b^{16} =\]
\[= \left( \frac{5}{4}a^{7}b^{8} \right)^{2} = \left( 1\frac{1}{4}a^{7}b^{8} \right)^{2}\ \]